Optimizing Elective Surgical Access: Integrated Strategies for Waiting-List Prioritization, Efficiency, Equity, and Clinical Outcomes - Valeria Hidalgo Figueroa; Susana María López Rojas; Keren Abigail Saynes Jarquin; Ana Carla Naranjo González; Pedro Aníbal Bailón de la O; Jaime Héctor Cisneros Sandoval; Blas David Santana Perez; Martín Ham San Martín (IECCMEXICO, 2026)
Surgical waiting lists represent a major challenge for healthcare systems because prolonged delays can affect not only service efficiency but also patient function, quality of life, equity of access, and clinical outcomes. This study analyzed the principal strategies used to manage elective surgical waiting lists, with emphasis on patient prioritization, referral management, cancellation prevention, perioperative efficiency, and dynamic reassessment. A structured review of the literature was conducted using evidence from systematic reviews, comparative studies, prioritization models, and clinical investigations evaluating the consequences of delayed surgery. The findings showed that multidimensional strategies provide a more comprehensive approach than systems based exclusively on chronological order or fixed urgency categories. Structured and dynamic prioritization models were particularly relevant because they incorporate variables such as pain, disease severity, comorbidities, functional impairment, expected surgical benefit, accumulated waiting time, and risk of deterioration. Referral management and prevention of avoidable cancellations were also identified as important mechanisms for improving operational efficiency and reducing unnecessary delays. In addition, prolonged waiting was associated with measurable deterioration in health-related quality of life, functional status, psychological well-being, and patient satisfaction in several surgical populations. The evidence supports the use of integrated management models combining clinical prioritization, periodic reassessment, coordinated referral pathways, efficient use of surgical capacity, and continuous monitoring of patient-centered and organizational outcomes. Effective waiting-list management should therefore aim not only to reduce the number of days to surgery, but also to ensure timely, equitable, and clinically appropriate access to elective surgical care.